2018
DOI: 10.1186/s12884-018-1926-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of community-based health services in influencing postnatal care visits in the Builsa and the West Mamprusi districts in rural Ghana

Abstract: BackgroundGlobally, maternal mortality is still a challenge. In Ghana, maternal morbidity and mortality rates remain high, particularly in rural areas. Postnatal Care (PNC) is one of the key strategies for improving maternal health. This study examined determinants of at least three PNC visits in rural Ghana.MethodsWe conducted a cross-sectional study at the Community-Based Health Planning and Services (CHPS) Zones in the Builsa and West Mamprusi Districts between April and June 2016. We selected 650 women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 35 publications
10
45
3
Order By: Relevance
“…We also found that, compliance with ANC clinic attendance in the index pregnancy (having 4 or more ANC visits) were found to increase the compliance with the PNC visits. Similar studies from Ethiopia, Ghana and Indonesia supported this finding [9,[55][56][57]. The positive health-seeking behavior among those with higher ANC attendance might be the reason.…”
Section: Discussionsupporting
confidence: 74%
“…We also found that, compliance with ANC clinic attendance in the index pregnancy (having 4 or more ANC visits) were found to increase the compliance with the PNC visits. Similar studies from Ethiopia, Ghana and Indonesia supported this finding [9,[55][56][57]. The positive health-seeking behavior among those with higher ANC attendance might be the reason.…”
Section: Discussionsupporting
confidence: 74%
“…The study found that frequency of ANC visit had signi cant association with utilization of the complete post natal care. This nding was in tandem with prior studies done in Ghana in 2016, where mother with four and more antenatal visits were 5.23 times more likely to receive CPNC [19]. It has been known that antenatal care exposes pregnant women to counseling and education about their own health and care of their children and may be particularly advantageous for those mothers and newborns in limiting settings, where health seeking behaviors are inadequate and access to health services is limited [2,4].In addition, women who make at least four ANC attendances are more likely to be those who adhere to health recommendations and therefore with higher chance of complying with the required number of PNC visits [19].…”
Section: Discussionsupporting
confidence: 86%
“…This nding was in tandem with prior studies done in Ghana in 2016, where mother with four and more antenatal visits were 5.23 times more likely to receive CPNC [19]. It has been known that antenatal care exposes pregnant women to counseling and education about their own health and care of their children and may be particularly advantageous for those mothers and newborns in limiting settings, where health seeking behaviors are inadequate and access to health services is limited [2,4].In addition, women who make at least four ANC attendances are more likely to be those who adhere to health recommendations and therefore with higher chance of complying with the required number of PNC visits [19]. The potential reason behind this could be, as a mother had more frequent contact with health care providers, she might have more chance to be counseled on the importance of PNC, its availability, recommended timing and targeted frequency of postnatal visits, and could result in CPNC utilization.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations